Strategic Framework for Character IP Development Using Design Thinking and Transmedia Storytelling in Indonesia - Tengku Salwa Nabila Johan; Sonny Rustiadi (Journal of Entrepreneurship & Business, 2026)
Purpose: This research aims to develop a strategic framework to resolve the critical "Execution Gap" faced by emerging character-based Intellectual Property (IP) brands, focusing specifically on the micro-enterprise ChasingDreams. Operating within the growing Indonesian "Healing Economy," the study investigates how leveraging Design Thinking and Transmedia Storytelling can effectively enhance consumer trust and influence financial behavior by transforming impulsive purchases into meaningful emotional investments. Method: This research employed a qualitative, exploratory single-case study design, structured around Design Thinking principles. Methodological triangulation was used, integrating the Resource-Based View (RBV), Customer Journey Mapping (CJM), and the AISAS model to diagnose the case company’s internal capabilities and pinpoint external customer friction points in purchase decision-making. Result: Findings reveal that ChasingDreams suffers from an "Unused Competitive Advantage" due to a Strategy-Structure Gap, leading to consumer validation deficits and purchase deferral. The study concludes by proposing a framework anchored in transmedia micro-narratives and radical transparency to bridge the gap between creative potential and commercial sustainability.